HOW TRAINING AND SKILLS DEVELOPMENT IMPROVE EMPLOYEE'S PERFORMANCE, MORAL, AND MOTIVATION - Baten, Abdul (Academic Research Centre Services, 2017)
Ready Made Garments (RMG) became a huge sector in Bangladesh. This sector is contributing tremendously to our economy. Nippon Garments Ltd. (NGL) is in RMG sector which is a sister concern of Abedin Group of Industries. NGL try to follow all the rules and regulations of labor laws by labor ministry of the government of Bangladesh. They maintain all compliances properly so that it won?t be harmful to the employees and environment. Training and development are one of the crucial components of Human Resource Management (HRM), besides all of the things like recruitment, selection, and, compensation. Training and development help an organization to motivate the employees in the work place and increase skills, productivity, and confidence for effective performance. To become successful and run an organization efficiently, it is very important to maintain good HR practices. When an organization has strong HR practices, and everyone in the company follow all the rules and regulations properly then the organization can create a healthy working environment which makes everyone happy. To follow all the rules and policies for growth, an organization should train the employees as per their training needs. HR always help to find the better ways to motivate employees through training and other facilities because if employees are not happy in their workplace, then they become less productive and quit the company. As a result, turnover is going to go up. Nippon Garments Ltd. is a project of Abedin Group of Industries, and it started its operation in 1984, and during the time NGL have faced so many ups and downs, but till now it has been successful in keeping its brand reputation. NGL also established competitive work environment and proved to become the number one RMG factory in Bangladesh. It is 100% export oriented garments factory. They input their best efforts to create a remarkable reputation in the RMG sector. They have both foreign and local customers, and their main customers are from Europe. They always try to give the best quality products to their customers, and for this, they are very much conscious about the raw materials used to make their end product. They import their basic fabric from China, Pakistan, Hong Kong, and India. Regarding of innovation, they are always up to date about the fashion trends and styles. Their main products are the jacket, pant, jogging & tracksuit, trouser, and more. They build up a strong relationship with the workers and employees and they also take necessary actions to maintain the strong relationship.